Potential of using vetiver grass to remediate soil contaminated with heavy metals - Minh, Vo Van; Khanh, Nguyen Van; Khoa, Le Van (VNU Journal of Science: Earth and Environmental Sciences, 2011)
Abstract. Vetiver grass is a plant with strong vitality in harsh conditions. This grass is now being applied widely in the field of soil erosion in the world. In this study, we evaluated the ability of vetiver grass to absorb some of heavy metals in the soil as Cd, Zn, Cu and Pb to determine the viability of using this species in remediation of soil contaminated. Research results showed that the absorption of heavy metals of this species was low (coefficient of BF and TF <1). However, as a result of high biomass, Vetiver  grass can absorb and remove heavy metals greatly from the soil. After 3 months planting, vetiver grass has accumulated from 0.05 to 0.23mg Cd /10kg soil; from 19.78 to 39.51mg Zn /10kg soil; from 0.68 to 3.35mg Cu /10kg soil; from 0.28 to 5.87mg Pb /10kg soil. It is 10 to 100 times higher than the hyper-accumulation species such as Brassica juncea, Thlaspi caerulescens, and Arabidopsis hallerii. These results demonstrate that the use of Vetiver grass for remediation of soil contaminated with heavy metal is feasible. Keywords: vetiver, heavy metals, soil contaminated, remediation, phytoremediation.